Effect of bFGF and fibroblasts combined with hyaluronic acid-based hydrogels on soft tissue augmentation: an experimental study in rats - Su Yeon Lee; Yongdoo Park; Soon Jung Hwang (SpringerOpen, 2019)
Abstract Background Hyaluronic acid (HA) has been applied as a primary biomaterial for temporary soft tissue augmentation and as a carrier for cells and the delivery of growth factors to promote tissue regeneration. Although HA derivatives are the most versatile soft tissue fillers on the market, they are resorbed early, within 3 to 12 months. To overcome their short duration, they can be combined with cells or growth factors. The purpose of this study was to investigate the stimulating effects of human fibroblasts and basic fibroblast growth factors (bFGF) on collagen synthesis during soft tissue augmentation by HA hydrogels and to compare these with the effects of a commercial HA derivative (Restylane®). Methods The hydrogel group included four conditions. The first condition consisted of hydrogel (H) alone as a negative control, and the other three conditions were bFGF-containing hydrogel (HB), human fibroblast-containing hydrogel (HF), and human fibroblast/bFGF-containing hydrogel (HBF). In the Restylane® group (HGF), the hydrogel was replaced with Restylane® (R, RB, RF, RBF). The gels were implanted subdermally into the back of each nude mouse at four separate sites. Twelve nude mice were used for the hydrogel (n = 6) and Restylane® groups (n = 6). The specimens were harvested 8 weeks after implantation and assessed histomorphometrically, and collagen synthesis was evaluated by RT-PCR. Results The hydrogel group showed good biocompatibility with the surrounding tissues and stimulated the formation of a fibrous matrix. HBF and HF showed significantly higher soft tissue synthesis compared to H (p < 0.05), and human collagen type I was well expressed in HB, HF, and HBF; HBF showed the strongest expression. The Restylane® filler was surrounded by a fibrous capsule without any soft tissue infiltration from the neighboring tissue, and collagen synthesis within the Restylane® filler could not be observed, even though no inflammatory reactions were observed. Conclusion This study revealed that HA-based hydrogel alone or hydrogel combined with fibroblasts and/or bFGF can be effectively used for soft tissue augmentation.